Influence of cryodestruction of hypertrophic tonsilla lingualis on the state of immune response - A. V. Аndreev; B. A. Nasibullin; I. K. Таgunova (Kazimierz Wielki University, 2017)
The authors based on a comprehensive examination of 32 patients with tonsilla lingualis hypertrophy who underwent the cryodestruction operation established that the overall condition of patients after the operation improved. Decreased manifestations of inflammatory reactions in the nasopharynx and oropharynx, its objective state. The study of the state of the immune response showed a decrease in the activity of autoimmune reactions to the tonsilla lingualis and the restoration of the cellular component of the immune response. As for the indices of his humoral component, they were partially improved, partially unchanged. The authors believe that such a discrepancy indicates a decrease in inflammatory reactions, but the preservation of dysregulation of this part of the immune system.